2017
DOI: 10.1002/cphc.201700346
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Stable Dianions by Functionalizing Polycyclic Aromatic Hydrocarbons

Abstract: Using density functional theory, we have carried out a systematic study of the stability and electronic properties of neutral and multiply charged molecules B C X (n=0, 1, 2; X=H, F, CN). Our main objective is to explore if the replacements of core C atoms and/or H atoms in naphthalene (C H ) can enhance the stability of their dianions. Indeed, we find that the dianions of B C (CN) are more stable than their monoanions with energies of 0.61 eV, 0.57 eV, and 1.97 eV for n=0, 1, 2, respectively. In addition, pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The most straightforward approach is to install electron-withdrawing substitutions to polycyclic aromatic hydrocarbons (PAHs). Among various electron-withdrawing groups, imide and nitrile are the most frequently employed for this purpose. Theoretical studies revealed some unique advantages of polynitrile PAHs as electron acceptors. However, the current synthetic strategies toward aryl imide and aryl nitriles lack the scope and adaptability to put multiple imide and nitrile groups on one PAH core.…”
mentioning
confidence: 99%
“…The most straightforward approach is to install electron-withdrawing substitutions to polycyclic aromatic hydrocarbons (PAHs). Among various electron-withdrawing groups, imide and nitrile are the most frequently employed for this purpose. Theoretical studies revealed some unique advantages of polynitrile PAHs as electron acceptors. However, the current synthetic strategies toward aryl imide and aryl nitriles lack the scope and adaptability to put multiple imide and nitrile groups on one PAH core.…”
mentioning
confidence: 99%